2020
DOI: 10.1371/journal.pone.0226806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental creatine and guanidinoacetic acid on spatial memory and the brain of weaned Yucatan miniature pigs

Abstract: The emergence of creatine as a potential cognitive enhancement supplement for humans prompted an investigation as to whether supplemental creatine could enhance spatial memory in young swine. We assessed memory performance and brain concentrations of creatine and its precursor guanidinoacetic acid (GAA) in 14-16-week-old male Yucatan miniature pigs supplemented for 2 weeks with either 200 mg/kg�d creatine (+Cr; n = 7) or equimolar GAA (157 mg/kg�d) (+GAA; n = 8) compared to controls (n = 14). Spatial memory te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Guanidinoacetic acid (GAA) is the only precursor of creatine (Cr) in vertebrates and can be methylated to Cr by guanidinoacetate N-methyltransferase (GAMT) (1)(2)(3)(4)(5)(6)(7)(8)(9). Cr acts as a unique energy buffer in the daily life of vertebrates (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Guanidinoacetic acid (GAA) is the only precursor of creatine (Cr) in vertebrates and can be methylated to Cr by guanidinoacetate N-methyltransferase (GAMT) (1)(2)(3)(4)(5)(6)(7)(8)(9). Cr acts as a unique energy buffer in the daily life of vertebrates (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Guanidinoacetic acid (GAA) is the only precursor of creatine (Cr) in vertebrates and can be methylated to Cr by guanidinoacetate N-methyltransferase (GAMT) (1)(2)(3)(4)(5)(6)(7)(8)(9). Cr acts as a unique energy buffer in the daily life of vertebrates (5)(6)(7)(8). As a nutritive feed additive, GAA has been approved by the EFSA (European Food Safety Authority) (10,11) and the FDA (U. S. Food and Drug Administration) (12) for poultry and swine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, research has examined whether creatine supplementation affects cognition, memory, and/or executive function in older individuals as well as patients with mild cognitive impairment [ 94 , 168 , 174 , 177 , 178 ]. Several studies have found that creatine supplementation attenuates mental fatigue [ 27 , 28 , 127 ] and/or can improve cognition, executive function, and/or memory [ 28 , 94 , 127 , 168 , 177 , 179 ]. For example, Watanabe and associates [ 180 ] found that creatine supplementation (8 g/day for 5 days) increased oxygen utilization in the brain and reduced mental fatigue in participants performing repetitive mathematical calculations.…”
Section: Role Of Creatine In Aging Populationsmentioning
confidence: 99%